Effect of Phaleria macrocarpa (Scheff.) Boerl Dry Extract to the Level of Malondialdehyde - Meiyanti Meiyanti; Eveline Margo; Juni Chudri (Global Medical & Health Communication (GMHC), 2020)
Increased age causes an increase in degenerative diseases. Antioxidants in the body unable to neutralize the increased concentration of free radicals. The flesh of the Phaleria macrocarpa (Scheff.) Boerl contains flavonoids which have antioxidant effects. At present, there are still very limited clinical trials of Phaleria macrocarpa (Scheff.) Boerl. This study was an experimental pretest and posttest involving 30 healthy volunteers receiving glucose loads in November 2018–February 2019 in Jakarta. This study aimed to assess the antioxidant effect of  Phaleria macrocarpa (Scheff.) Boerl dry fruit extract in various dosage ranges. Subjects of this study aged 30–55 years. The data collection included anthropometric examination and malondialdehyde levels before and after administration of dry fruit extract doses of 62.5 mg, 125 mg, and 250 mg at 150 minutes after oral glucose induction. Data analysis using a paired t test with p<0.05. Decreased levels of malondialdehyde in the administration of Phaleria macrocarpa (Scheff.) Boerl with a dose of 62.5 mg, 125 mg, and 250 mg by 40.9%, 22.9%, and 18.3% compared to the baseline malondialdehyde level (1,608 nmol/mL). Statistical analysis using a paired t test showed p=0.000 for all three doses compared with baseline levels. Dry fruit extract of Phaleria macrocarpa (Scheff.) Boerl has an antioxidant effect; the antioxidant effect of the extract is not directly proportional to the dose. EFEK ANTIOKSIDAN EKSTRAK KERING PHALERIA MACROCARPA (SCHEFF.) BOERL TERHADAP KADAR MALONDIALDEHIDPertambahan usia menyebabkan peningkatan penyakit degeneratif. Antioksidan dalam tubuh tidak mampu menetralkan peningkatan konsentrasi radikal bebas. Daging buah Phaleria macrocarpa (Scheff.) Boerl mengandung flavonoid mempunyai efek antioksidan. Saat ini masih sangat terbatas uji klinis Phaleria macrocarpa (Scheff.) Boerl. Penelitian ini merupakan uji eksperimental sebelum dan sesudah perlakuan pada 30 sukarelawan sehat yang diinduksi dengan glukosa yang dilaksanakan pada bulan November 2018–Februari 2019 di Jakarta. Penelitian ini bertujuan menilai efek antioksidan ekstrak kering buah Phaleria macrocarpa (Scheff.) Boerl dalam beberapa kisaran dosis yang diberikan. Subjek penelitian berusia 30–55 tahun. Pengumpulan data meliputi pemeriksaan antropometri serta kadar malondialdehid sebelum dan sesudah pemberian ekstrak kering dosis 62,5 mg, 125 mg, dan 250 mg pada menit 150 setelah dilakukan induksi glukosa oral. Analisis data menggunakan uji t berpasangan dengan p<0,05. Penurunan kadar malondialdehid pada pemberian ekstrak Phaleria macrocarpa (Scheff.) Boerl dosis 62,5 mg, 125 mg, dan 250 mg sebesar 40,9%, 22,9%, dan 18,3% dibanding dengan kadar malondialdehid sebelum pemberian (1.608 nmol/mL). Analisis statistik menggunakan uji t berpasangan didapatkan p=0,000 untuk ketiga dosis dibanding dengan kadar awal. Ekstrak kering buah Phaleria macrocarpa (Scheff.) Boerl mempunyai efek antioksidan; efek antioksidan ekstrak tidak berbanding lurus dengan dosis.